Esterno e interno nella pandemia: persistenza e risignificazione degli spazi pubblici e domestici dal punto di vista di genere in tempi di lockdown (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
By means of a “gender topography” of the pandemic, the essay proposes a reflection meant to capture the links between the transformations of public and domestic spaces in the context of the emergency and the different gender condition in which women and men inhabit those spaces. As for the domestic space, the issue of gender-based violence is addressed by observing the responses to the paradox of lock-down, which forced women to live together for a long time with their abusers in a confined space. As for the public space, the essay analyzes the reaction against the persistency of male-only decision-making structures throughout the pandemic, looking in particular at decree-law 86/2020, by which, using for the first time the surrogate power of art. 120 Cost., the national Government acted for the legislative body of Puglia, enforcing the so-called “gender double preference” in the electoral law.
Keywords: Gender analysis; lockdown; violence against women; electoral equal opportunities; surrogate power